Perubahan Iklim sebagai Penyebab Terjadinya Kekerasan dan Migrasi: Studi Kasus Konflik Darfur - Nur Inna Alfiyah (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2016)
Migration has always identified with people movement to avoid the occurrence of violence or to seek a better life. It has lasted from the beginning until today, but not many people are aware that migration and violence was also fueled by climate change, not only war and natural disasters. The linkage between climate change and the appearance of a conflict cannot be seen directly, it needs to see the root reasons of the conflicts itselselves. But seen from some of the acts of violence that occurred in some countries such as African countries, violence has always triggered by competition over scarce natural resources such as waters. So this article will be focussing on how the linkages between climate change problems that could encourage violence as well as the causes of migration, by linking the impact of geopolitical and environmental degradation.